A low-density nickel-based high-temperature alloy and preparation method thereof
By optimizing the chemical composition and heat treatment process of nickel-based high-temperature alloys, a microstructure with low density, high temperature mechanical properties and toughness is formed, and the existing nickel-based high-temperature alloys are solved, and are suitable for high-temperature structural parts of aerospace engines Preparation.
Patent Information
- Application Number
- CN202310019575.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-01-06
Smart Images

Figure CN116219231B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nickel-based high-temperature alloys, and in particular to a low-density nickel-based high-temperature alloy and a preparation method thereof. Background Art
[0002] Nickel-based high-temperature alloys have become the preferred material for high-temperature structural parts of advanced aerospace engines due to their excellent mechanical properties and temperature resistance.
[0003] With the increasing demand for economic benefits of air transportation, the fuel efficiency of aerospace engines needs to be greatly improved, which has led to the continuous improvement of the high-temperature performance of high-temperature alloy components; however, the density of the alloy gradually increases, which increases the overall weight of the engine and reduces fuel efficiency. If high-density alloys are used to make high-temperature alloy blades, it is easy to cause cracks in the blades and turbine disks and cause them to be scrapped prematurely. Therefore, under the premise of ensuring strength, the alloy density is first controlled to reduce the centrifugal force on the blades and turbine disks and reduce the weight of the engine to improve the safety and fuel economy of the engine.
[0004] In summary, there is an urgent need for a nickel-based high-temperature alloy that has low density, high high-temperature mechanical properties and toughness. Summary of the invention
[0005] In view of this, the present invention provides a low-density nickel-based high-temperature alloy and a preparation method thereof, the main purpose of which is to provide and prepare a nickel-based high-temperature alloy having low density, high high-temperature mechanical properties and toughness.
[0006] In order to achieve the above object, the present invention mainly provides the following technical solutions:
[0007] In one aspect, an embodiment of the present invention provides a low-density nickel-based high-temperature alloy, wherein the chemical composition of the low-density nickel-based high-temperature alloy is as follows, in terms of weight percentage:
[0008] C: 0.02-0.17wt%, preferably 0.05-0.15wt%;
[0009] Cr: 8.0-10.5wt%, preferably 8.5-9.6wt%;
[0010] Co: 4.0-5.6wt%, preferably 4.5-5.5wt%;
[0011] W: 5.0-8.5wt%, preferably 6.5-8.0wt%;
[0012] Mo: 2.0-4.5wt%, preferably 2.5-3.5wt%;
[0013] Al: 5.0-7.0wt%, preferably 5.6-6.3wt%;
[0014] Nb: 1.5-2.6wt%, preferably 2-2.5wt%;
[0015] Y: 0.001-0.06wt%, preferably 0.01-0.05wt%;
[0016] B: 0.001-0.045wt%, preferably 0.01-0.034wt%;
[0017] Hf: 0.5-2.0wt%, preferably 1.0-1.7wt%;
[0018] Mg: 0-0.003wt%, preferably 0-0.001wt%;
[0019] Ca 0-0.003wt%, preferably 0-0.001wt%;
[0020] Ni is the remainder.
[0021] Preferably, in the low-density nickel-based high-temperature alloy, the content of the strengthening phase γ′ phase forming element satisfies the following condition: the sum of the Al element and the Hf element is greater than or equal to 7.0 wt % and less than or equal to 8.0 wt %.
[0022] Preferably, in the low-density nickel-based high-temperature alloy, trace elements C, Y, and B satisfy the following conditions: the sum of the contents of element C, element Y, and element B is greater than or equal to 0.075wt% and less than or equal to 0.14wt%.
[0023] Preferably, in the low-density nickel-based high-temperature alloy, the Mg element meets the following conditions: greater than 0 and less than or equal to 0.001 wt %.
[0024] Preferably, in the low-density nickel-based high-temperature alloy, the Ca element meets the following conditions: greater than 0 and less than or equal to 0.001 wt %.
[0025] Preferably, the density of the low-density nickel-based high-temperature alloy is 8.0 g / cm 3 -8.3g / cm 3 .
[0026] Preferably, the initial melting temperature of the low-density nickel-based high-temperature alloy measured by metallographic method is 1200-1220°C.
[0027] Preferably, the interaction between Mg, Hf and C elements promotes the formation of granular M in low-density nickel-based high-temperature alloys. 23 C6 type carbide; preferably, the granular M 23 The formation sites of C6 carbides include interdendritic sites of the alloy.
[0028] Preferably, the interaction between Mg, Ca, Y and Al elements promotes the formation of compounds containing Y, Mg and Al elements in the low-density nickel-based high-temperature alloy. Preferably, the compound containing Y, Mg and Al elements is (Al, Mg)2Y; preferably, the formation position of the compound containing Y, Mg and Al elements includes the interdendritic eutectic position.
[0029] Preferably, if the low-density nickel-based high-temperature alloy is an equiaxed high-temperature alloy, the microstructure of the low-density nickel-based high-temperature alloy includes a matrix γ phase, a strengthening phase γ′ phase, a skeleton carbide phase and a granular carbide phase; wherein the volume fraction of the strengthening phase γ′ phase is 50-60%, the volume fraction of the skeleton carbide phase is 0.001-1%, the volume fraction of the granular carbide phase is 0-0.005% (preferably 0.001-0.005%), the volume fraction of the eutectic is 0.01-0.5%, and the rest is the γ phase; preferably, in the low-density nickel-based high-temperature alloy, the size of the carbide is 1-500μm, the size of the micropore is 50-500μm, and the grain size is 0.5-20mm. Here, during the high-temperature deformation process, the skeleton carbide and the granular carbide play a coordinating role in the deformation process, which can reduce the harmful effects of the micropores and eutectics and improve the mechanical properties of the alloy.
[0030] Preferably, if the low-density nickel-based high-temperature alloy is a directional columnar crystal high-temperature alloy or a single crystal high-temperature alloy, the microstructure of the low-density nickel-based high-temperature alloy includes a matrix γ phase, a strengthening phase γ′ phase, a skeleton carbide phase and a granular carbide phase; wherein the volume fraction of the strengthening phase γ′ phase is 50-60%, the volume fraction of the skeleton carbide phase is 0.001-1%, the volume fraction of the granular carbide phase is 0-0.005% (preferably 0.001-0.5%), the volume fraction of the eutectic is 0.01-0.6%, and the rest is the γ phase; preferably, in the low-density nickel-based high-temperature alloy, the size of the carbide is 1-600μm, and the size of the micropore is 10-100μm. Here, relative to equiaxed crystals, for directional columnar crystals or single crystals, due to the slow solidification rate, the eutectic content increases, but the shrinkage compensation ability of the alloy is improved, so the micropore size is reduced, so that the mechanical properties of the alloy are improved.
[0031] Preferably, the long-lasting strength life of the low-density nickel-based high-temperature alloy under the conditions of 1020℃ / 137MPa is greater than 80h; the long-lasting strength life of the low-density nickel-based high-temperature alloy under the conditions of 760℃ / 500MPa is greater than or equal to 45h; the long-lasting strength life of the low-density nickel-based high-temperature alloy under the conditions of 980℃ / 216MPa is greater than or equal to 25h; the long-lasting strength life of the low-density nickel-based high-temperature alloy under the conditions of 1000℃ / 135MPa is greater than or equal to 60h.
[0032] Preferably, the low-density nickel-based high-temperature alloy is a directional columnar crystal high-temperature alloy or a single crystal high-temperature alloy, and the preparation method comprises the following steps:
[0033] Melting steps: After vacuum induction melting of the alloy raw materials, they are cast into master alloy ingots, which are then polished to remove oxide scale.
[0034] Directional solidification step: using a directional solidification process to prepare the polished master alloy ingot into a directional columnar crystal high-temperature alloy part or a single crystal high-temperature alloy part;
[0035] Heat treatment step: heat treating the oriented columnar crystal high temperature alloy part or the single crystal high temperature alloy part to obtain a low-density nickel-based high temperature alloy;
[0036] Preferably, in the directional solidification step, the pouring temperature is 320-360°C higher than the initial melting temperature of the low-density nickel-based high-temperature alloy; preferably, the mold shell temperature is consistent with the pouring temperature; or the mold shell temperature is 20-30°C higher than the pouring temperature;
[0037] Preferably, in the smelting step, high-temperature refining is performed first and then low-temperature refining; wherein, Ca element is added to the melt in the low-temperature refining stage; after low-temperature refining, the melt is naturally cooled, and when a film appears on the surface of the alloy melt, high-purity argon gas is filled into the vacuum furnace, and when the amount of argon gas filled reaches 3-5Pa, Mg element is added, and then the melt is heated to 1550±20℃ for casting to obtain a mother alloy ingot; further preferably, the temperature of the high-temperature refining is 1550±20℃; the temperature of the low-temperature refining is 100±30℃ above the alloy liquidus.
[0038] Preferably, the low-density nickel-based high-temperature alloy is an equiaxed high-temperature alloy, and the preparation method comprises the following steps:
[0039] Melting step: After vacuum induction melting of the alloy raw materials, casting into a master alloy ingot, and then grinding the master alloy ingot to remove the oxide scale;
[0040] Equiaxed directional solidification step: performing equiaxed solidification treatment on the polished master alloy ingot to obtain an equiaxed high-temperature alloy part;
[0041] Heat treatment step: heat treating the equiaxed high temperature alloy part to obtain a low-density nickel-based high temperature alloy;
[0042] Preferably, the refining temperature in the smelting step is 1550-1600° C. to volatilize the Mg element;
[0043] Preferably, in the step of equiaxed solidification treatment: the pouring temperature is 150-200° C. higher than the initial melting temperature of the low-density nickel-based high-temperature alloy, and the mold shell temperature is 350-480° C. lower than the pouring temperature;
[0044] Preferably, in the smelting step, high-temperature refining is performed first and then low-temperature refining; wherein, Ca element is added to the melt in the low-temperature refining stage; after low-temperature refining, the melt is naturally cooled, and when a film appears on the surface of the alloy melt, high-purity argon gas is filled into the vacuum furnace, and when the amount of argon gas filled reaches 3-5Pa, Mg element is added, and then the melt is heated to 1550±20℃ for casting to obtain a mother alloy ingot; further preferably, the temperature of the high-temperature refining is 1550±20℃; the temperature of the low-temperature refining is 100±30℃ above the alloy liquidus.
[0045] Preferably, the heat treatment step comprises:
[0046] Solution homogenization treatment: the high temperature alloy part is kept at a temperature of 1200-1220°C for 3.8-4.2h, and then cooled in air or inert gas (preferably argon) to obtain a high temperature alloy after solution homogenization treatment; wherein the high temperature alloy part is any one of a directional columnar crystal high temperature alloy part, a single crystal high temperature alloy part, and an equiaxed crystal high temperature alloy part; preferably, the high temperature alloy part is placed in a heat treatment furnace and heated to 1200-1220°C at a heating rate of 8±2°C / min to prevent deformation or cracking of the alloy part due to excessive heating;
[0047] Primary aging treatment: keeping the high-temperature alloy after the solid solution homogenization treatment at a temperature of 1090-1110° C. for 3.8-4.2 hours, cooling in air or inert gas (preferably argon) to obtain a high-temperature alloy after the primary aging treatment; preferably, heating the high-temperature alloy after the solid solution homogenization treatment to 1090-1110° C. at a heating rate of 15±2° C. / min to prevent deformation of the alloy part;
[0048] Secondary aging treatment: the high-temperature alloy after the primary aging treatment is kept at a temperature of 860-880°C for 23.8-24.2h, and cooled in air or inert gas (preferably argon) to obtain a low-density nickel-based high-temperature alloy; preferably, the high-temperature alloy after the primary aging treatment is heated to 860-880°C at a heating rate of 20±2°C / min to prevent deformation of the alloy part.
[0049] Compared with the prior art, the low-density nickel-based high-temperature alloy and the preparation method thereof of the present invention have at least the following beneficial effects:
[0050] On the one hand, an embodiment of the present invention provides a low-density nickel-based high-temperature alloy, wherein the chemical composition of the low-density nickel-based high-temperature alloy is as follows: C 0.02-0.17wt% (preferably 0.05-0.15wt%), Cr8.0-10.5wt% (preferably 8.5-9.6wt%), Co 4.0-5.6wt% (preferably 4.5-5.5wt%), W5.0-8.5wt% (preferably 6.5-8.0wt%), Mo2.0-4.5wt% (preferably 2.5-3.5wt%), Al5.0-7.0wt% (preferably 5.6-6.3wt%), Nb 1.5-2.6wt% (preferably 2-2.5wt%), Y0.001-0.06wt% (preferably 0.01-0.05w%), B 0.001-0.045wt% (preferably 0.01-0.034wt%), Hf 0.5-2.0wt% (preferably 1.0-1.7wt%), Mg 0-0.003wt%, (preferably 0-0.001wt%), Ca 0-0.003wt% (preferably 0-0.001wt%); Ni is the balance. Preferably, the sum of Al element and Hf element is greater than or equal to 7.0wt% and less than or equal to 8.0wt%; preferably, the sum of the content of C element, Y element and B element is greater than or equal to 0.075wt% and less than or equal to 0.14wt%. Here, through the design of the above chemical composition (element content and synergistic effect between elements), the nickel-based high-temperature alloy not only has the characteristics of low density and low cost, but also has high high-temperature mechanical properties and toughness, good organizational stability, and is particularly suitable for the preparation of high-temperature components in the fields of aerospace, aviation, ships, petrochemicals, etc. In addition, it should be noted that the addition of Mg has a very good effect on the strength of high-temperature alloys. It can play the following roles: (1) The volatilization of Mg and C elements during the smelting process is beneficial to deep deoxidation and other impurity elements; (2) Mg and Hf have a synergistic effect: Since a certain amount of Hf element is added to the alloy, the addition of Hf element will increase the eutectic content in the alloy, which is not conducive to the improvement of performance, while the magnesium element remaining in the alloy is easy to segregate at the interface of the alloy eutectic / matrix, improving the deformation coordination ability of the eutectic / matrix interface during deformation and relieving stress concentration. (3) The carbon content in the alloy of this application is relatively high. During the solidification process, C is easy to segregate between dendrites or grain boundaries. The interaction between Mg and C in the alloy can reduce the segregation of Nb, Hf, and C elements at the grain boundaries, which is beneficial to refine the morphology of carbides and promote the decomposition of large MC-type carbides. In addition, in addition to Mg, Ca and Y elements are also added.First, the addition of Ca can remove oxygen from the alloy. By adding Mg and Y, not only a higher yield can be obtained, but also a compound rich in Y, Mg, and Al is promoted. Through the composition analysis of electron microscope, the compound is rich in Y, Mg, and Al, and its size is only about 1 micron and spherical. This is because during the solidification process, elements such as Y and Mg are easily enriched in the liquid phase of the alloy, and the compound is formed in the later stage of solidification. The formation of this compound consumes the Al element in the liquid phase of the alloy, thereby reducing the volume fraction of the eutectic in the alloy, which is beneficial to improving the performance of the alloy and increasing the endurance life of the alloy 1040℃ / 137MPa from 11h to 82h. In addition, after adding Ca, Ca combines with oxygen to form calcium oxide, which can serve as a nucleation point for compounds containing Y, Mg, and Al elements, prompting the compound to form preferentially near calcium oxide; the addition of Ca not only plays a role in purifying the alloy, but also promotes the formation of compounds and is beneficial to improving performance.
[0051] On the other hand, an embodiment of the present invention provides a method for preparing the above-mentioned low-density nickel-based high-temperature alloy, specifically, using a directional solidification process to prepare a master alloy ingot into a directional columnar crystal high-temperature alloy part or a single crystal high-temperature alloy part; then, the directional columnar crystal high-temperature alloy part or the single crystal high-temperature alloy part is heat treated to obtain a low-density nickel-based high-temperature alloy. Preferably, in the directional solidification step, the pouring temperature is 320-360°C higher than the initial melting temperature of the low-density nickel-based high-temperature alloy; preferably, the heat treatment step includes: (1) solution homogenization treatment (maintaining at a temperature of 1200-1220°C for 3.8-4.2 hours, followed by air cooling or argon cooling to room temperature), (2) primary aging treatment (maintaining at a temperature of 1090-1110°C for 3.8-4.2 hours, followed by air cooling or argon cooling to room temperature), (3) primary aging treatment (maintaining at a temperature of 860-880°C for 23.8-24.2 hours, followed by air cooling or argon cooling to room temperature). Here, according to the chemical composition of the alloy, the corresponding The above steps are designed to avoid broken crystal defects and improve the mechanical properties of the alloy. For example, since the alloy contains a certain amount of Hf and C elements, the pouring temperature of the alloy cannot be too high. Pouring at too high a temperature will cause an interface reaction between the ceramic shell and the alloy, which will not only lead to a decrease in the key elements Hf and C in the alloy, but may also prevent the dendrite structure from growing continuously during the directional solidification process, resulting in defects such as broken crystals, thereby reducing the mechanical properties of the alloy. In addition, the above-mentioned heat treatment system of the present invention, on the one hand, optimizes the size volume analysis of the γ′ strengthening phase in the alloy, and most importantly, the heat treatment process can promote the decomposition of Hf-containing carbides, so that M is precipitated in the matrix. 23 C6 type carbide has a lattice constant close to that of the matrix and precipitates at grain boundaries or phase boundaries, hindering the movement of dislocations on grain boundaries or phase interfaces, thereby improving the mechanical properties of the alloy.
[0052] In summary, the density of the low-density nickel-based high-temperature alloy provided in the embodiment of the present invention is 8.0-8.3 g / cm 3 , has a high initial melting temperature (1200-1220℃), high endurance strength limit and creep limit, very good high-temperature and medium-temperature endurance performance, good tensile properties and endurance plasticity, good processing performance, and the alloy is not prone to thermal cracking when used to prepare directionally solidified columnar crystal components, and has high production efficiency.
[0053] In addition, the low-density nickel-based high-temperature alloy with the above-mentioned composition design provided in the embodiment of the present invention has a unique feature of wide applicability. Specifically, it can be processed into directional columnar crystals, single crystals, and equiaxed crystals, and has excellent mechanical properties. It should be noted here that achieving one component and multiple uses is closely related to the composition of the alloy. The three alloys of columnar crystals, single crystals, and equiaxed crystals are very critical to the formation of the organization during the solidification process. First, there are a lot of grain boundaries during the solidification of equiaxed crystals. The present invention forms carbides at the grain boundaries by adding elements such as C and B to enhance the strength of the grain boundaries. Secondly, when directional solidification of high-temperature alloy parts with complex structures, the alloy's ability to resist the formation of thermal cracks is one of the key factors for whether it can be applied, because the higher ability to resist the formation of thermal cracks can make the castings obtain a higher pass rate and reduce the preparation cost. In the present invention, the Hf element is added to promote the formation of liquid film during the solidification process and reduce the tendency to form thermal cracks. Finally, for single crystals, their initial melting temperature is a very critical factor. Usually, the addition of Hf elements can significantly reduce the initial melting temperature of the alloy. The present invention adopts the addition of elements such as Mg and Y, and through the interaction of elements such as Al and Hf, significantly reduces the content of eutectic in the alloy, increases the initial melting temperature of the alloy, and makes the initial melting temperature of the alloy as high as 1200-1220°C.
[0054] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 is the Larson-Miller curve of the alloy prepared in Example 3 of the present invention and the existing DZ417G alloy;
[0056] Figure 2 is a typical organization diagram of the oriented columnar crystal high temperature alloy of Example 1; wherein, Figure 2 (a) is the organization diagram; (b) is the microscopic organization diagram (high magnification);
[0057] Figure 3This is the microstructure morphology of the alloy after heat treatment in Example 3;
[0058] Figure 4 : are typical organization diagrams of alloys prepared in the embodiments of the present invention; wherein, Figure a is a typical organization diagram of an equiaxed crystal high-temperature alloy prepared in Example 5; Figure b is a typical organization diagram of an oriented columnar crystal high-temperature alloy prepared in Example 2; Figure c is a typical organization diagram of a single crystal high-temperature alloy prepared in Example 4;
[0059] Figure 5 is the cast microstructure diagram of equiaxed high-temperature alloy; among them, Figure 5 Figure (a) is a microstructure diagram showing carbides of the equiaxed crystal high temperature alloy prepared in Example 1 (without the addition of magnesium element), Figure (b) is a microstructure diagram showing carbides of the equiaxed crystal high temperature alloy prepared in Example 5 (with the addition of magnesium element), Figure (c) is a microstructure diagram showing internal micropores of the equiaxed crystal high temperature alloy prepared in Example 1 (without the addition of magnesium element), and Figure (d) is a microstructure diagram showing internal micropores of the equiaxed crystal high temperature alloy prepared in Example 5 (with the addition of magnesium element).
[0060] Figure 6 is a microstructure diagram of the heat-treated state of the equiaxed high-temperature alloy prepared in Example 5;
[0061] Figure 7 is an electron image of the equiaxed high-temperature alloy prepared in Example 5;
[0062] Figure 8 is a cast microstructure diagram showing eutectic of an equiaxed high temperature alloy; wherein, Figure 8 Figure (a) is a microstructure diagram showing eutectic of the equiaxed crystal high-temperature alloy prepared in Example 1 (without adding magnesium element), and Figure (b) is a microstructure diagram showing eutectic of the equiaxed crystal high-temperature alloy prepared in Example 5 (with adding magnesium element and Y element). DETAILED DESCRIPTION
[0063] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention application are described in detail below in conjunction with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.
[0064] On the one hand, an embodiment of the present invention provides a low-density nickel-based high-temperature alloy, wherein the chemical composition of the low-density nickel-based high-temperature alloy is as follows, in weight percentage: C 0.02-0.17wt% (preferably 0.05-0.15wt%), Cr 8.0-10.5wt% (preferably 8.5-9.6wt%), Co 4.0-5.6wt% (preferably 4.5-5.5wt%), W 5.0-8.5wt% (preferably 6.5-8.0wt%), Mo 2.0-4.5wt% (preferably 2.5-3.5wt%), Al 5.0-7.0wt% (preferably 5.6-6.3wt%), Nb 1.5-2.6wt% (preferably 2-2.5wt%), Y 0.001-0.06wt% (preferably 0.01-0.05w%), B 0.001-0.045wt% (preferably 0.01-0.034wt%), Hf 0.5-2.0wt% (preferably 1.0-1.7wt%), Mg 0-0.003wt%, (preferably 0-0.001wt%), Ca 0-0.003wt% (preferably 0-0.001wt%); Ni is the balance. Preferably, in the low-density nickel-based high-temperature alloy: the sum of Al element and Hf element is greater than or equal to 7.0wt% and less than or equal to 8.0wt%. The sum of the content of C element, Y element and B element is greater than or equal to 0.075wt% and less than or equal to 0.14wt%.
[0065] Preferably, the density of the low-density nickel-based high-temperature alloy is 8.0 g / cm 3 -8.3g / cm 3 (Here, low density mainly refers to: a relatively high content of Al elements, which makes the alloy density small. In addition, the content of refractory elements W, Mo, and Nb cannot be too much, otherwise the alloy density will be large.) The initial melting temperature of the low-density nickel-based high-temperature alloy measured by metallographic method is 1200-1220°C. Preferably, the low-density nickel-based high-temperature alloy consists of a matrix γ phase, a strengthening phase γ′ phase and a carbide phase, wherein the volume fraction of the strengthening phase γ′ phase is 50-55%, the volume fraction of the carbide phase is 0.001-1%, and the rest is the γ phase. Preferably, the low-density nickel-based high-temperature alloy has a long-lasting strength life of more than 80h under 1020°C / 137MPa conditions.
[0066] Regarding the above-mentioned low-density nickel-based high-temperature alloy, it should be noted that the composition design principle is as follows:
[0067] (1) The role of Cr in nickel-based high-temperature alloys is to increase the ability to resist oxidation, corrosion and solid solution strengthening. When the alloy contains more strengthening elements such as W, Mo, Nb, Ta, etc., too much Cr will reduce the structural stability of the alloy and cause the precipitation of topological close-packed phase (TCP). The alloy of the present invention contains only a small amount of Mo, and the performance can be improved by increasing the Cr content. Here, the Cr content in the alloy is controlled to 8.5-10.0wt%
[0068] (2) Mo also plays a role in solid solution strengthening and can increase the γ / γ′ mismatch, making the dislocation network at the γ / γ′ two-phase interface denser, thereby improving the alloy performance. However, excessive Mo will also lead to the precipitation of harmful phases. Here, the content of Mo in the alloy of the present invention is 2.5-3.5wt%, which improves the alloy performance but does not lead to the precipitation of harmful phases.
[0069] (3) The main effects of Co include solid solution strengthening, increasing the volume fraction of γ′ phase, improving the plasticity and hot working properties of the alloy, and improving the structural stability. At the same time, Co can reduce the stacking fault energy of the matrix, improve the alloy's endurance strength and creep resistance. The content of Co in the alloy of the present invention is controlled to be 4.5-5.5wt% so that it can fully exert the above properties.
[0070] (4) Al and Hf are both γ′ phase-forming elements, which determine the amount of strengthening phases in the alloy and the strengthening effect. The strength of the alloy can be improved by adding a relatively large amount of aluminum and titanium elements (7.0wt%≤Al+Hf≤8.0wt%) to form a phase with a high volume fraction. At the same time, the addition of Hf elements can effectively improve the strength of the grain boundaries of the alloy, and under the premise of ensuring that the alloy has a high initial melting temperature, it can reduce the tendency of the alloy to form thermal cracks during the directional solidification process, so that it has higher process performance.
[0071] (5) Directionally solidified high-temperature alloys contain a large number of grain boundaries. Elements such as C, B and Y are added to the alloy of the present invention to strengthen the grain boundaries and interdendritic regions. On the other hand, they form carbides with Cr to strengthen the alloy. The content of grain boundary strengthening elements in the alloy is 0.075wt%≤C+Y+B≤0.14wt%.
[0072] (6) In the alloy of the present invention, by adding the W element and the Hf element in the above-mentioned content range, not only the mechanical properties of the alloy are synergistically improved, but also the addition of the Hf element with the above-mentioned set composition can improve the alloy's resistance to thermal cracking, making the alloy particularly suitable for the preparation of thin-walled components. Under normal circumstances, for nickel-based high-temperature alloys, the aluminum content is increased in order to obtain higher strength. Unlike conventional technologies, the Al content of the present invention is not high, and by adding the Hf element, the content of the strengthening phase (γ′ phase) is synergistically increased to improve the mechanical properties of the alloy. The content of refractory elements in the alloy of the present invention is small.
[0073] (7) Regarding the low-density nickel-based high-temperature alloy of the above chemical composition of the present invention, it should be emphasized that it has a unique feature: it can be processed into oriented columnar crystals, single crystals, and equiaxed crystals, and has excellent mechanical properties. However, in conventional technology, the alloy composition suitable for oriented columnar crystals is not suitable for processing into single crystals and equiaxed crystals, otherwise cracks and poor mechanical properties will occur (the alloy composition suitable for single crystals is not suitable for processing into columnar crystals and equiaxed crystals, otherwise cracks and poor mechanical properties will occur; and the alloy composition suitable for equiaxed crystals is not suitable for processing into columnar crystals and single crystals, otherwise cracks and poor mechanical properties will occur).
[0074] Here is an explanation from the principle why the low-density nickel-based high-temperature alloy with the above chemical composition of the present invention has a wide range of applications (it can be processed into oriented columnar crystals, single crystals, and equiaxed crystals): (1) The content of refractory elements in the low-density nickel-based high-temperature alloy with the above chemical composition of the present invention is relatively small. During the directional solidification process, it will not cause a large amount of component segregation, and is more suitable for large-sized components; (2) Because the alloy contains the above-mentioned content of C and Hf, the mechanical properties of the alloy can be improved and the probability of defect formation during solidification can be reduced (it can be seen that the present invention is suitable for the preparation of equiaxed crystals); (3) In general single crystal high-temperature design, the carbon content is controlled to be low; while the low-density nickel-based high-temperature alloy with the above chemical composition of the present invention has a higher carbon content. Since the content of refractory elements is relatively low, refractory carbides are formed by C, which further improves the mechanical properties of the alloy (it can be seen that it is suitable for the preparation of single crystals).
[0075] (8) The addition of Mg has a very good effect on the strength of high-temperature alloys. It can play the following roles: (1) The volatilization of Mg and C elements during the smelting process is beneficial to deep deoxidation and other impurity elements; (2) Mg and Hf have a synergistic effect: Since a certain amount of Hf element is added to the alloy, the addition of Hf element will increase the eutectic content in the alloy, which is not conducive to the improvement of performance, while the magnesium element remaining in the alloy is easy to segregate at the interface of the alloy eutectic / matrix, improving the deformation coordination ability of the eutectic / matrix interface during deformation and relieving stress concentration. (3) The carbon content in the alloy of this application is relatively high. During the solidification process, C is easy to segregate between dendrites or grain boundaries. The interaction between Mg and C in the alloy can reduce the segregation of Nb, Hf, and C elements at the grain boundaries, which is beneficial to refine the morphology of carbides and promote the decomposition of large MC-type carbides.
[0076] Furthermore, the synergistic effect of the above alloying elements is further described as follows:
[0077] (1) In the alloy of the present invention, see Figure 5As shown in the figure, the synergistic effect of the added Mg element with Hf and C not only changes the morphology of carbides, but also improves the fluidity of the alloy and reduces the microporosity of the alloy. This is because the synergistic effect of Mg and other elements such as Hf and C changes the morphology of MC-type carbides from skeleton to granular. The beneficial effect of this change is to improve the fluidity of the alloy, which increases the fluidity of the alloy during the solidification process, so it can reduce the micro-shrinkage in the alloy and improve the density of the alloy. In addition, see Figure 6 As shown in the figure, the addition of Mg and the action of Hf and other elements form granular M near MC carbides and around the eutectic. 23 C6 carbide (see Figure 6 As shown by the arrow in FIG. 1 ; In addition, the granular M 23 The formation position of C6 type carbide mainly includes the interdendritic position of the alloy, preferably also includes the grain boundary, low-angle grain boundary, and subgrain boundary position), M 23 C6 carbides can coordinate deformation and improve the performance of the alloy, increasing its high-temperature endurance performance from 28.98h to 51.48h under 980℃ / 216MPa conditions.
[0078] (2) In addition to Mg, Ca and Y are added to the alloy of the present invention. First, the addition of Ca can remove oxygen from the alloy. Then, by adding Mg and Y, not only a higher yield can be obtained, but also a compound rich in Y, Mg, and Al can be promoted. Figure 7 As shown. Through the composition analysis of electron microscope, the compound is rich in Y, Mg, and Al elements, and its size is only about 1 micron and spherical. This is because during the solidification process, elements such as Y and Mg are easily enriched in the liquid phase of the alloy, and in the later stage of solidification, the compound is formed. The formation of this compound consumes the Al element in the alloy liquid phase, thereby reducing the volume fraction of eutectic in the alloy (see Figure 8 As shown), it is beneficial to improve the performance of the alloy, and the endurance life of the alloy at 1040℃ / 137MPa is increased from 11h to 82h. The compound containing Y, Mg and Al elements is (Al, Mg)2Y; preferably, the formation position of the compound containing Y, Mg and Al elements includes the interdendritic eutectic position.
[0079] On the other hand, an embodiment of the present invention provides a method for preparing a low-density nickel-based high-temperature alloy, wherein the low-density nickel-based high-temperature alloy is an oriented columnar crystal high-temperature alloy or a single crystal high-temperature alloy, and the method comprises the following steps:
[0080] Melting step: After the alloy components are subjected to conventional batching and vacuum induction melting, they are cast into a master alloy ingot, and then the master alloy ingot is polished to remove oxide scale.
[0081] Directional solidification step: using a directional solidification process to prepare the master alloy ingot into a directional columnar crystal high-temperature alloy part or a single crystal high-temperature alloy part (blade blank or rod blank); wherein, in the directional solidification step, the pouring temperature is 320-360°C higher than the initial melting temperature of the low-density nickel-based high-temperature alloy; wherein the mold shell temperature is consistent with the pouring temperature or the mold shell temperature is 20-30°C higher than the pouring temperature.
[0082] Heat treatment step: heat treating the oriented columnar crystal high temperature alloy part or the single crystal high temperature alloy part to obtain a low-density nickel-based high temperature alloy.
[0083] In another aspect, an embodiment of the present invention provides a method for preparing a low-density nickel-based high-temperature alloy, wherein the low-density nickel-based high-temperature alloy is an equiaxed high-temperature alloy, and the preparation method comprises the following steps:
[0084] Melting step: After vacuum induction melting of the alloy raw materials, casting into a master alloy ingot, and then grinding the master alloy ingot to remove the oxide scale;
[0085] Equiaxed directional solidification step: performing equiaxed solidification treatment on the polished master alloy ingot to obtain an equiaxed high-temperature alloy part;
[0086] Heat treatment step: heat treating the equiaxed high temperature alloy part to obtain a low-density nickel-based high temperature alloy;
[0087] Preferably, in the step of fine equiaxed solidification treatment: the pouring temperature is 150-200°C higher than the initial melting temperature of the low-density nickel-based high-temperature alloy, and the mold shell temperature is 350-480°C lower than the pouring temperature.
[0088] Preferably, in the above preparation method, the heat treatment step comprises:
[0089] Solid solution homogenization treatment: keeping the oriented columnar crystal high temperature alloy at a temperature of 1200-1220° C. for 3.8-4.2 hours, and cooling to obtain the oriented columnar crystal high temperature alloy after solid solution homogenization treatment;
[0090] Primary aging treatment: keeping the oriented columnar crystal high temperature alloy after the solid solution homogenization treatment at a temperature of 1090-1110° C. for 3.8-4.2 hours, and cooling the oriented columnar crystal high temperature alloy after the primary aging treatment to obtain;
[0091] Secondary aging treatment: The oriented columnar crystal high temperature alloy after the primary aging treatment is kept at a temperature of 860-880° C. for 23.8-24.2 hours, and then cooled to obtain a low-density nickel-based high temperature alloy.
[0092] In addition, in the above preparation method, in order to make the Mg element play a better role, since the activity of Mg is very high, the yield rate in the alloy smelting process is very low, so a certain amount of Ca element is also added in the present invention. The present invention optimizes the method of adding Ca and Mg elements in the alloy, firstly performs high-temperature refining, performs high-temperature refining in the range of 1550±20℃, performs low-temperature refining at the alloy liquidus of 100℃, and adds Ca element during low-temperature refining, so that the oxygen element in the alloy is preferentially combined with Ca, so that the oxygen content in the alloy is reduced to below 10ppm. Subsequently, the melt is naturally cooled and cooled. When a film appears on the surface of the alloy melt, high-purity argon is filled in the vacuum furnace. When the amount of argon filled is 3-5Pa, Mg element is added, and then the temperature is raised to 1550±20°C for pouring. By adopting this method, not only can the Mg element in the alloy be evenly distributed in the alloy, but also the recovery rate of the Mg element can be significantly improved. By using the method of the present invention, the recovery rate of the Mg element can be increased to more than 80%, which can well promote the effect of Mg with elements such as C and Hf, so that the alloy composition and performance can be stably controlled.
[0093] In addition, it should be further emphasized that the present invention mainly changes the microstructure of the alloy and improves the mechanical properties of the alloy through the interaction of trace elements. In the present invention, the interaction of elements such as Mg and Hf promotes the 23 It should be noted that: the prior art believes that one of the important functions of hafnium is to inhibit the precipitation of M 23 C6 or M6C carbides are precipitated in large quantities along the grain boundaries, and can form secondary stable fine, dispersed, irregular MC (mainly HfC particles) with the carbon released by the decomposition of MC. However, unlike the prior art, the present invention precipitates M in the alloy by combining the alloy composition design and the heat treatment process (short heat treatment time). 23 C6 type carbide, the precipitation of this carbide improves the mechanical properties of the alloy.
[0094] The solid solution homogenization treatment in the preparation method of the present invention is as follows: the high temperature alloy is kept at a temperature of 1200-1220°C for 3.8-4.2 hours, and then cooled by air or argon; the primary aging treatment is as follows: the high temperature alloy after the solid solution homogenization treatment is kept at a temperature of 1090-1110°C for 3.8-4.2 hours, and then cooled by air or argon; the secondary aging treatment is as follows: the high temperature alloy after the solid solution homogenization treatment is kept at a temperature of 860-880°C for 23.8-24.2 hours, and then cooled by air or argon to obtain a low density nickel-based high temperature alloy. In the solid solution homogenization treatment, the holding time and the holding temperature range are narrower, because the present invention adds elements rich in Y, Mg, Al, Ca, Hf, etc., which can promote the compounds of Y, Mg, Al elements and M 23The formation of C6 type carbides, but the optimal precipitation temperature of these compounds is controlled by the heat treatment conditions. Through a lot of research, it is found that under the preparation conditions of the present invention, the alloy can obtain more precipitation phases, so that the alloy has better mechanical properties.
[0095] The following is further described by specific experimental examples:
[0096] Example 1
[0097] Example 1: Prepare a low-density nickel-based high-temperature alloy.
[0098] The chemical composition of the low-density nickel-based high-temperature alloy of this embodiment is shown in Table 1.
[0099] Table 1 (wt%)
[0100] C Cr Co W Mo Al Nb Y B Hf Mg Ni 0.03 8.5 4.5 5.5 2.5 5.5 1.8 0.005 0.001 0.5 0.001 margin
[0101] The specific preparation steps are as follows:
[0102] Vacuum induction furnace smelting: After conventional batching and vacuum induction smelting according to the alloy composition described in Table 1, cast into a master alloy ingot with a size of 80×500mm, then grind the master alloy ingot to remove the oxide scale and cut into suitable blocks (master alloy ingot blocks). In this step, high-temperature refining (1550℃) is first performed, and then low-temperature refining (100℃ above the alloy liquidus); after low-temperature refining, the melt is naturally cooled and cooled. When a film appears on the surface of the alloy melt, high-purity argon is filled in the vacuum furnace. When the amount of argon filled reaches 3-5Pa, Mg element is added, and then the melt is heated to 1550℃ for casting to obtain a master alloy ingot.
[0103] Directional solidification step: Directional solidification treatment is performed on the master alloy ingot (block), specifically as follows: a directional solidification furnace is used for directional solidification treatment; wherein the temperature gradient of the directional solidification furnace is about 50K / cm, the pouring temperature is 1520°C, wherein the mold shell temperature is consistent with the pouring temperature; after keeping warm for 10 minutes, pulling is performed at a predetermined growth rate of 6mm / min to prepare a directional columnar crystal high-temperature alloy specimen.
[0104] After analysis, the density of the oriented columnar crystal superalloy sample is 8.0g / cm 3 , the initial melting temperature is 1200℃; the microstructure of the oriented columnar crystal high-temperature alloy sample is composed of matrix γ phase, strengthening phase γ′ phase and carbide phase, among which the volume fraction of the strengthening phase γ′ phase is about 50%, the volume fraction of the skeleton carbide phase is 0.001%, the volume fraction of the granular carbide phase is 0.001%, the volume fraction of the eutectic is 0.01%, and the rest is γ phase, the size of the carbide is 1μm, and the size of the micropore is 10μm.
[0105] Heat treatment step: heat treating the oriented columnar crystal high temperature alloy to obtain a low-density nickel-based high temperature alloy.
[0106] Among them, the heat treatment system is as follows:
[0107] (1) Solution homogenization treatment: keep at 1200°C for 3.8 hours (wherein the heating rate to 1200°C is 8°C / min), and then air cool to room temperature;
[0108] (2) Primary aging treatment: keeping at 1090°C for 3.8 hours (wherein the heating rate to 1090°C is 15°C / min), followed by air cooling to room temperature;
[0109] (3) Secondary aging treatment: keeping at 860°C for 23.8 hours (wherein the heating rate to 860°C is 20°C / min), and then air cooling to room temperature.
[0110] The performance of the low-density nickel-based high-temperature alloy of this embodiment was tested and compared with the DZ417G alloy. The specific results are shown in Tables 2 and 3.
[0111] Table 2 is a comparison of typical tensile properties of the low-density nickel-based high-temperature alloy prepared in Example 1 and the DZ417G alloy.
[0112] Table 2
[0113]
[0114] It can be clearly seen from Table 2 that the tensile properties of the low-density nickel-based high-temperature alloy prepared in the embodiment of the present invention are far superior to those of the DZ417G alloy.
[0115] Table 3 Comparison of typical temperature endurance properties of the low-density nickel-based high-temperature alloy prepared in Example 1 and DZ417G.
[0116] Table 3
[0117]
[0118] It can be clearly seen from Table 3 that the temperature endurance performance of the low-density nickel-based high-temperature alloy prepared in the embodiment of the present invention is far superior to that of the DZ417G alloy.
[0119] Example 2
[0120] Example 2: Prepare a low-density nickel-based high-temperature alloy.
[0121] The chemical composition of the low-density nickel-based high-temperature alloy of this embodiment is shown in Table 4.
[0122] Table 4 (wt%)
[0123]
[0124] The specific preparation steps are as follows:
[0125] Vacuum induction furnace smelting: After conventional batching and vacuum induction smelting according to the alloy composition described in Table 4, cast into a master alloy ingot with a size of 80×500mm, then grind the master alloy ingot to remove the oxide scale, and cut into suitable blocks (master alloy ingot blocks). Among them, high-temperature refining is carried out first, and then low-temperature refining is carried out; wherein, Ca element is added to the melt during the low-temperature refining stage; after low-temperature refining, the melt is naturally cooled and cooled, and when a film appears on the surface of the alloy melt, high-purity argon gas is filled in the vacuum furnace, and Mg element is added when the amount of argon gas filled reaches 3-5Pa, and then the melt is heated to 1550℃ for casting to obtain a master alloy ingot; wherein, the temperature of the high-temperature refining is 1550℃; the temperature of the low-temperature refining is 120℃ above the alloy liquidus.
[0126] Directional solidification step: Directional solidification treatment is performed on the master alloy ingot (block), specifically as follows: a directional solidification furnace is used for directional solidification treatment; wherein the temperature gradient of the directional solidification furnace is about 50K / cm, the pouring temperature is 1575°C, wherein the mold shell temperature is consistent with the pouring temperature; after keeping warm for 10 minutes, pulling is performed at a predetermined growth rate of 2mm / min to prepare a directional columnar crystal high-temperature alloy specimen.
[0127] After analysis, the density of the oriented columnar crystal superalloy sample is 8.3g / cm 3 , the initial melting temperature is 1220℃; the microstructure of the oriented columnar superalloy sample consists of matrix γ phase, strengthening phase γ′ phase and carbide phase, among which the volume fraction of strengthening phase γ′ phase is about 60%, the volume fraction of skeleton carbide phase is 1%, the volume fraction of granular carbide phase is 0.005%, the volume fraction of eutectic is 0.6%, and the rest is γ phase. The size of carbide is 600μm, and the size of micropore is 100μm.
[0128] Heat treatment step: heat treating the oriented columnar crystal high temperature alloy to obtain a low-density nickel-based high temperature alloy.
[0129] Among them, the heat treatment system is as follows:
[0130] (1) Solution homogenization treatment: keep at 1205°C for 4.2 hours (wherein the heating rate to 1205°C is 8°C / min), and then air cool to room temperature;
[0131] (2) Primary aging treatment: keeping at 1095°C for 4.2 hours (wherein the heating rate to 1095°C is 15°C / min), followed by air cooling to room temperature;
[0132] (3) Secondary aging treatment: keeping at 880°C for 24.2 hours (wherein the heating rate to 880°C is 20°C / min), and then air cooling to room temperature.
[0133] The performance of the low-density nickel-based high-temperature alloy of this embodiment was tested and compared with the DZ417G alloy, as shown in Tables 5 and 6 for details.
[0134] Table 5 is a comparison of typical tensile properties of the low-density nickel-based high-temperature alloy prepared in Example 2 and the DZ417G alloy.
[0135] Table 5
[0136]
[0137] It can be clearly seen from Table 5 that the tensile properties of the low-density nickel-based high-temperature alloy prepared in the embodiment of the present invention are far superior to those of the DZ417G alloy.
[0138] Table 6 is a comparison of typical temperature endurance properties of the low-density nickel-based high-temperature alloy prepared in Example 2 and DZ417G.
[0139] Table 6
[0140]
[0141] It can be clearly seen from Table 6 that the temperature endurance performance of the low-density nickel-based high-temperature alloy prepared in the embodiment of the present invention is far superior to that of the DZ417G alloy.
[0142] Example 3
[0143] Example 3: Prepare a low-density nickel-based high-temperature alloy.
[0144] The chemical composition of the low-density nickel-based high-temperature alloy of this embodiment is shown in Table 7.
[0145] Table 7 (wt%)
[0146] C Cr Co W Mo Al Nb Y B Hf Mg Ca Ni 0.1 9.5 5.0 6.5 3.0 6.0 2.2 0.03 0.02 1.5 0.002 0.001 margin
[0147] The specific preparation steps are as follows:
[0148] Vacuum induction furnace smelting: After conventional batching and vacuum induction smelting according to the alloy composition described in Table 7, cast into a master alloy ingot with a size of 80×500mm, then grind the master alloy ingot to remove the oxide scale, and cut into suitable blocks (master alloy ingot blocks). Among them, high-temperature refining is first carried out, and then low-temperature refining is carried out; wherein, Ca element is added to the melt during the low-temperature refining stage; after low-temperature refining, the melt is naturally cooled and cooled, and when a film appears on the surface of the alloy melt, high-purity argon gas is filled in the vacuum furnace, and Mg element is added when the amount of argon gas filled reaches 3-5Pa, and then the melt is heated to 1560℃ for casting to obtain a master alloy ingot; wherein, the temperature of the high-temperature refining is 1560℃; the temperature of the low-temperature refining is 130℃ above the alloy liquidus.
[0149] Directional solidification step: Directional solidification treatment is performed on the master alloy ingot (block), specifically as follows: a directional solidification furnace is used for directional solidification treatment; wherein the temperature gradient of the directional solidification furnace is about 50K / cm, the pouring temperature is 1550°C, wherein the mold shell temperature is consistent with the pouring temperature; after keeping warm for 10 minutes, pulling is performed at a predetermined growth rate of 6mm / min to prepare a directional columnar crystal high-temperature alloy specimen.
[0150] After analysis, the density of the oriented columnar crystal superalloy sample is 8.2g / cm 3 , the initial melting temperature is 1220℃; the microstructure of the oriented columnar superalloy sample is composed of matrix γ phase, strengthening phase γ′ phase and carbide phase, among which the volume fraction of strengthening phase γ′ phase is 55%, the volume fraction of skeleton carbide phase is 0.005%, the volume fraction of granular carbide phase is 0.003%, the volume fraction of eutectic is 0.2%, and the rest is γ phase. The size of carbide is 300μm, and the size of micropore is 30μm. .
[0151] Heat treatment step: heat treating the oriented columnar crystal high temperature alloy to obtain a low-density nickel-based high temperature alloy.
[0152] Among them, the heat treatment system is as follows:
[0153] (1) Solution homogenization treatment: keep at 1220°C for 4 hours (wherein the heating rate to 1220°C is 8°C / min), and then air cool to room temperature;
[0154] (2) Primary aging treatment: keeping at 1100°C for 4 hours (wherein the heating rate to 1100°C is 15°C / min), followed by air cooling to room temperature;
[0155] (3) Secondary aging treatment: keep at 870°C for 24 hours (wherein the heating rate to 870°C is 20°C / min), and then air cool to room temperature.
[0156] The performance of the low-density nickel-based high-temperature alloy of this embodiment was tested and compared with the DZ417G alloy, as shown in Tables 8 and 9 for details.
[0157] Table 8 is a comparison of typical tensile properties of the low-density nickel-based high-temperature alloy prepared in Example 3 and the DZ417G alloy.
[0158] Table 8
[0159]
[0160] It can be clearly seen from Table 8 that the tensile properties of the low-density nickel-based high-temperature alloy prepared in the embodiment of the present invention are far superior to those of the DZ417G alloy.
[0161] Table 9 is a comparison of typical temperature endurance properties of the low-density nickel-based high-temperature alloy prepared in Example 3 and DZ417G.
[0162] Table 9
[0163]
[0164] It can be clearly seen from Table 9 that the temperature endurance performance of the low-density nickel-based high-temperature alloy prepared in the embodiment of the present invention is far superior to that of the DZ417G alloy.
[0165] in addition, Figure 1 : is the Larson-Miller curve of the oriented columnar crystal high temperature alloy prepared in Example 3 and the existing DZ417G alloy. Figure 1 It can be seen that: at the high temperature stage, the directional columnar crystal high-temperature alloy prepared in Example 3 has obvious advantages in terms of endurance strength.
[0166] Figure 2 is a typical organization diagram of the oriented columnar crystal high temperature alloy of Example 1. Figure 2 It can be seen that the alloy is composed of columnar crystals, and the alloy structure is composed of y′ phase, carbides, etc. The formation of columnar crystals can improve the mechanical properties of the alloy. At the same time, the carbides on the grain boundaries can prevent the sliding of the grain boundaries at high temperatures, thereby improving the mechanical properties.
[0167] Figure 3 The as-cast structure and heat-treated structure of the oriented columnar crystal high-temperature alloy prepared in Example 3 are compared. Figure 3 It can be seen that a higher carbide content is beneficial to improving the strength of the alloy. Heat treatment can reduce the uniform distribution of the y′ phase in the alloy and the precipitation of small cubic y′ phases with regular arrangement, while promoting the decomposition of the carbide phase, making the organization stable and easy to control, thereby enhancing the effect of hindering dislocation movement and improving creep strength.
[0168] Example 4
[0169] Example 4 prepares a low-density nickel-based high-temperature alloy.
[0170] The chemical composition of the low-density nickel-based high-temperature alloy of this embodiment is shown in Table 10.
[0171] Table 10 (wt%)
[0172] C Cr Co W Mo Al Nb Y B Hf Mg Ni 0.05 9.5 5.0 6.5 3.0 6.3 2.2 0.03 0.02 1.0 0.001 margin
[0173] The specific preparation steps are as follows:
[0174] Vacuum induction furnace smelting: After conventional batching and vacuum induction smelting according to the alloy composition described in Table 10, cast into a master alloy ingot with a size of 80×500mm, then grind the master alloy ingot to remove the oxide scale and cut into suitable blocks (master alloy ingot blocks). In this step, high-temperature refining (1550°C) is first performed, and then low-temperature refining (120°C above the alloy liquidus); after low-temperature refining, the melt is naturally cooled and cooled. When conjunctiva appears on the surface of the alloy melt, high-purity argon is filled in the vacuum furnace. When the amount of argon filled reaches 3-5Pa, Mg element is added, and then the melt is heated to 1520°C for casting to obtain a master alloy ingot.
[0175] Directional solidification step: Directional solidification treatment is performed on the master alloy ingot (block), specifically as follows: Directional solidification treatment is performed in a directional solidification furnace; wherein, the ceramic shell used has a spiral crystal selector to facilitate the preparation of single crystals, the temperature gradient of the directional solidification furnace is about 50K / cm, and the pouring temperature is 1550°C, wherein the shell temperature is consistent with the pouring temperature; after keeping warm for 5 minutes, pulling is performed at a predetermined growth rate of 5mm / min to prepare a single crystal high-temperature alloy specimen.
[0176] After analysis, the density of the single crystal high temperature alloy sample is 8.2g / cm 3 , the initial melting temperature is 1220℃; the microstructure of the single crystal high temperature alloy sample is composed of matrix γ phase, strengthening phase γ′ phase and carbide phase, among which the volume fraction of strengthening phase γ′ phase is 58%, the volume fraction of skeleton carbide phase is 0.01%, the volume fraction of granular carbide phase is 0.002%, the volume fraction of eutectic phase is 0.08%, and the rest is γ phase. The size of carbide is 50μm, the size of micropore is 20μm, and the rest is γ phase.
[0177] Heat treatment step: heat treating the single crystal high temperature alloy to obtain a low-density nickel-based high temperature alloy.
[0178] Among them, the heat treatment system is as follows:
[0179] (1) Solution homogenization treatment: keep at 1220°C for 4 hours (wherein the heating rate to 1220°C is 8°C / min), and then air cool to room temperature;
[0180] (2) Primary aging treatment: keeping at 1100°C for 4 hours (wherein the heating rate to 1100°C is 15°C / min), followed by air cooling to room temperature;
[0181] (3) Secondary aging treatment: keep at 870°C for 24 hours (wherein the heating rate to 870°C is 20°C / min), and then air cool to room temperature.
[0182] The performance of the low-density nickel-based high-temperature alloy of this embodiment was tested and compared with the DD407 single crystal high-temperature alloy, as shown in Table 11 and Table 12.
[0183] Table 11 is a comparison of typical tensile properties of the low-density nickel-based single crystal high-temperature alloy prepared in Example 4 and the DD407 alloy.
[0184] Table 11
[0185]
[0186] It can be clearly seen from Table 11 that the tensile properties of the low-density nickel-based high-temperature alloy prepared in the embodiment of the present invention are far superior to those of the DZ417G alloy.
[0187] Table 12 is a comparison of the typical temperature endurance properties of the low-density nickel-based single crystal high-temperature alloy prepared in Example 4 and DD407.
[0188] Table 12
[0189]
[0190] It can be clearly seen from Table 12 that the temperature endurance performance of the low-density nickel-based single crystal high-temperature alloy prepared in the embodiment of the present invention is better than that of the DD407 single crystal high-temperature alloy.
[0191] Example 5
[0192] Example 5: Prepare a low-density nickel-based high-temperature alloy.
[0193] The chemical composition of the low-density nickel-based high-temperature alloy of this embodiment is shown in Table 13.
[0194] Table 13 (wt%)
[0195] C Cr Co W Mo Al Nb Y B Hf Mg Ca Ni 0.1 9.0 5.0 7.5 3.0 6.0 2.2 0.04 0.02 1.5 0.002 0.001 margin
[0196] The specific preparation steps are as follows:
[0197] Vacuum induction furnace smelting: After conventional batching and vacuum induction smelting according to the alloy composition described in Table 13, cast into a master alloy ingot with a size of 80×500mm, then grind the master alloy ingot to remove the oxide scale and cut into suitable blocks (master alloy ingot blocks). In this step, high-temperature refining (1540°C) is first performed, and then low-temperature refining (110°C above the alloy liquidus); after low-temperature refining, the melt is naturally cooled and cooled. When conjunctiva appears on the surface of the alloy melt, high-purity argon is filled in the vacuum furnace. When the amount of argon filled reaches 3-5Pa, Mg element is added, and then the melt is heated to 1550°C for casting to obtain a master alloy ingot.
[0198] The steps for preparing equiaxed crystals are as follows: the master alloy ingot (block) is subjected to directional solidification treatment, specifically: a vacuum induction furnace is used for melting and pouring, the pouring temperature is 1400°C, wherein the mold shell temperature is 920-1050°C; the equiaxed crystal high-temperature alloy specimen is prepared by keeping the temperature for more than 4 hours.
[0199] After analysis, the density of the equiaxed high-temperature alloy sample is 8.3g / cm 3 , the initial melting temperature is 1220℃; the microstructure of the equiaxed high temperature alloy sample is composed of matrix γ phase, strengthening phase γ′ phase and carbide phase, the volume fraction of strengthening phase γ′ phase is 53%, the volume fraction of skeleton carbide phase is 0.05%, the volume fraction of granular carbide phase is 0.01%, the volume fraction of eutectic is 0.5%, and the rest is γ phase. In the equiaxed alloy, the size of carbide is 500μm, the size of micropore is 500μm, and the size of grain is 20mm.
[0200] Heat treatment step: heat treating the equiaxed high temperature alloy to obtain a low-density nickel-based high temperature alloy.
[0201] Among them, the heat treatment system is as follows:
[0202] (1) Solution homogenization treatment: keep at 1220°C for 4 hours (wherein the heating rate to 1220°C is 8°C / min), and then air cool to room temperature;
[0203] (2) Primary aging treatment: keeping at 1100°C for 4 hours (wherein the heating rate to 1100°C is 15°C / min), followed by air cooling to room temperature;
[0204] (3) Secondary aging treatment: keep at 870°C for 24 hours (wherein the heating rate to 870°C is 20°C / min), and then air cool to room temperature.
[0205] The performance of the low-density nickel-based high-temperature alloy of this embodiment was tested and compared with the K4951 equiaxed nickel-based high-temperature alloy, see Table 14 and Table 15 for details.
[0206] Table 14 is a comparison of typical tensile properties of the low-density nickel-based equiaxed crystal high-temperature alloy prepared in Example 5 and the K4951 equiaxed crystal nickel-based high-temperature alloy.
[0207] Table 14
[0208]
[0209] It can be clearly seen from Table 14 that the tensile properties of the low-density nickel-based high-temperature alloy prepared in the embodiment of the present invention are better than those of the K4951 alloy.
[0210] Table 15 is a comparison of typical temperature endurance properties of the low-density nickel-based high-temperature alloy prepared in Example 5 and the K4951 equiaxed nickel-based high-temperature alloy.
[0211] Table 15
[0212]
[0213] It can be clearly seen from Table 15 that the temperature endurance performance of the low-density nickel-based equiaxed high-temperature alloy prepared in the embodiment of the present invention is better than that of the K4951 equiaxed nickel-based high-temperature alloy.
[0214] Figure 4 is a typical organization diagram of the alloy prepared in the embodiment of the present invention; wherein, Figure a is a typical organization diagram of the equiaxed crystal high temperature alloy prepared in Example 5; Figure b is a typical organization diagram of the oriented columnar crystal high temperature alloy prepared in Example 2; Figure c is a typical organization diagram of the single crystal high temperature alloy prepared in Example 4. Figure 4 It can be seen that the alloy with the chemical composition designed by the present invention can be processed into oriented columnar crystals, single crystals, and equiaxed crystals.
[0215] Comparative Example 1
[0216] Comparative Example 1 is compared with Example 5 in that: Mg and Ca elements are not added to the alloy chemical composition. The step of adding magnesium element is omitted in the corresponding smelting step; and the other steps are the same.
[0217] The equiaxed high temperature alloys prepared in Example 5 and Comparative Example 1 are compared as follows:
[0218] (1) Figure 5Figure (a) is a microstructure diagram showing carbides of the equiaxed crystal high temperature alloy prepared in Example 1 (without the addition of magnesium element), Figure (b) is a microstructure diagram showing carbides of the equiaxed crystal high temperature alloy prepared in Example 5 (with the addition of magnesium element), Figure (c) is a microstructure diagram showing internal micropores of the equiaxed crystal high temperature alloy prepared in Example 1 (without the addition of magnesium element), and Figure (d) is a microstructure diagram showing internal micropores of the equiaxed crystal high temperature alloy prepared in Example 5 (with the addition of magnesium element).
[0219] See also Figure 5 In the embodiment of the present invention, by adding Mg element, it works synergistically with Hf and C, which not only changes the morphology of carbides, but also improves the fluidity of the alloy and reduces the microporosity of the alloy. This is because the morphology of MC-type carbides is changed from skeleton to granular by the combined action of magnesium and hafnium and carbon and other elements. The beneficial effect of this change is to improve the fluidity of the alloy, so that the fluidity of the alloy during the solidification process is increased, so that the micro-shrinkage in the alloy can be reduced and the compactness of the alloy can be improved.
[0220] (2) Figure 6 : is the microstructure diagram of the heat-treated state of the equiaxed high-temperature alloy prepared in Example 5. Figure 6 It can be seen that the addition of Mg and the action of Hf and other elements form granular M near MC carbides and around the eutectic. 23 C6 carbide (M 23 The formation position of C6 type carbide is mainly between dendrites, and eutectic is also generated between dendrites). 23 C6 carbides can coordinate deformation and improve the performance of the alloy (increasing its endurance performance at 980℃ / 216MPa from 28.98h to 51.48h).
[0221] (3) Then, by adding Mg and Y elements, not only a higher yield can be obtained, but also a compound rich in Y, Mg, and Al elements is promoted; the compound containing Y, Mg, and Al elements is (Al, Mg)2Y, and its formation position includes the interdendritic eutectic position. Here, the Ca element combines with oxygen to form calcium oxide, which can serve as a nucleation point for the compound containing Y, Mg, and Al elements, prompting the compound to form preferentially near calcium oxide, such as Figure 7 As shown. Through the composition analysis of electron microscope, the compound is rich in Y, Mg, and Al elements, and its size is only about 1 micron and spherical. This is because during the solidification process, elements such as Y and Mg are easily enriched in the liquid phase of the alloy, and in the later stage of solidification, the compound is formed. The formation of this compound consumes the Al element in the alloy liquid phase, thereby reducing the volume fraction of eutectic in the alloy (see Figure 8As shown, the number of eutectics in (b) is significantly smaller than that in (a), which is beneficial to improving the performance of the alloy (increasing the endurance life of the alloy 1040℃ / 137MPa from 11h to 82h).
[0222] The properties of the equiaxed crystal alloy prepared in Example 5 and the equiaxed crystal alloy prepared in Comparative Example 1 are compared, as shown in Table 16.
[0223] Table 16
[0224]
[0225] It can be seen from Table 16 that in Example 5, the addition of Mg and Ca elements can significantly improve the mechanical properties of the alloy.
[0226] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A low-density nickel-based high-temperature alloy, characterized in that: The chemical composition of the low-density nickel-based high-temperature alloy is as follows, in weight percentage: C: 0.02-0.17wt%; Cr: 8.0-10.5wt%; Co: 4.0-5.6wt%; W: 5.0-8.5wt%; Mo: 2.0-4.5wt%; Al: 5.0-7.0wt%; Nb: 1.5-2.6wt%; Y: 0.001-0.06wt%; B: 0.001-0.045wt%; Hf: 0.5-2.0wt%; Mg: 0-0.003wt%; Ca: 0-0.003wt%; Ni is the remainder; The density of the low-density nickel-based high-temperature alloy is 8.0-8.3 g / cm 3 ; The initial melting temperature of the low-density nickel-based high-temperature alloy is measured by metallographic method to be 1200-1220°C; Wherein, if the low-density nickel-based high-temperature alloy is an equiaxed high-temperature alloy, then: the microstructure of the low-density nickel-based high-temperature alloy includes a matrix γ phase, a strengthening phase γ′ phase, a skeleton carbide phase and a granular carbide phase; wherein the volume fraction of the strengthening phase γ′ phase is 50-60%, the volume fraction of the skeleton carbide phase is 0.001-1%, the volume fraction of the granular carbide phase is 0-0.005%, the volume fraction of the eutectic is 0.01-0.5%, and the rest is the γ phase; Among them, if the low-density nickel-based high-temperature alloy is a directional columnar crystal high-temperature alloy or a single crystal high-temperature alloy, then: the microstructure of the low-density nickel-based high-temperature alloy includes a matrix γ phase, a strengthening phase γ′ phase, a skeleton carbide phase and a granular carbide phase; wherein the volume fraction of the strengthening phase γ′ phase is 50-60%, the volume fraction of the skeleton carbide phase is 0.001-1%, the volume fraction of the granular carbide phase is 0-0.005%, the volume fraction of the eutectic is 0.01-0.6%, and the rest is the γ phase.
2. The low-density nickel-based high-temperature alloy according to claim 1, characterized in that: In the low-density nickel-based high-temperature alloy: The weight percentage of C is 0.05-0.15wt%; and / or The weight percentage of Cr is 8.5-9.6wt%; and / or The weight percentage of Co is 4.5-5.5wt%; and / or The weight percentage of W is 6.5-8.0wt%; and / or The weight percentage of Mo is 2.5-3.5wt%; and / or The weight percentage of Al is 5.6-6.3wt%; and / or The weight percentage of Nb is 2-2.5wt%; and / or The weight percentage of Y is 0.01-0.05wt%; and / or The weight percentage of B is 0.01-0.034wt%; and / or The weight percentage of Hf is 1.0-1.7wt%; and / or The weight percentage of Mg is 0-0.001wt%; and / or The weight percentage of Ca is 0-0.001wt%.
3. The low-density nickel-based high-temperature alloy according to claim 1, characterized in that: In the low-density nickel-based high-temperature alloy, the content of the strengthening phase γ′ phase forming element meets the following conditions: the sum of the Al element and the Hf element is greater than or equal to 7.0wt% and less than or equal to 8.0wt%; and / or In the low-density nickel-based high-temperature alloy, trace elements C, Y, and B satisfy the following conditions: the sum of the contents of element C, element Y, and element B is greater than or equal to 0.075 wt % and less than or equal to 0.14 wt %.
4. The low-density nickel-based high-temperature alloy according to claim 3, characterized in that: In the low-density nickel-based high-temperature alloy: The Mg element satisfies the following conditions: greater than 0 and less than or equal to 0.001wt%; and / or The Ca element satisfies the following conditions: greater than 0 and less than or equal to 0.001 wt %.
5. The low-density nickel-based high-temperature alloy according to any one of claims 1 to 4, characterized in that: The interaction between Mg, Hf and C elements promotes the formation of granular M in low-density nickel-based high-temperature alloys. 23 C6 type carbide.
6. The low-density nickel-based high-temperature alloy according to claim 5, characterized in that: The granular M 23 The formation sites of C6 carbides include interdendritic sites of the alloy.
7. The low-density nickel-based high-temperature alloy according to any one of claims 1 to 4, characterized in that: The interaction between Mg, Ca, Y and Al elements promotes the formation of compounds containing Y, Mg and Al elements in low-density nickel-based high-temperature alloys.
8. The low-density nickel-based high-temperature alloy according to claim 7, characterized in that: The compound containing Y, Mg and Al elements is (Al, Mg)2Y.
9. The low-density nickel-based high-temperature alloy according to claim 7, characterized in that: The formation position of the compound containing Y, Mg and Al elements includes an interdendritic eutectic position.
10. The low-density nickel-based high-temperature alloy according to any one of claims 1 to 4, characterized in that: If the low-density nickel-based high-temperature alloy is an equiaxed high-temperature alloy, then: the volume fraction of the particulate carbide phase is 0.001-0.005%; and / or If the low-density nickel-based high-temperature alloy is an equiaxed high-temperature alloy, then: in the low-density nickel-based high-temperature alloy, the size of the carbides is 1-500 μm, the size of the micropores is 50-500 μm, and the size of the grains is 0.5-20 mm; and / or If the low-density nickel-based high-temperature alloy is a directional columnar crystal high-temperature alloy or a single crystal high-temperature alloy, then: the volume fraction of the granular carbide phase is 0.001-0.005%; and / or If the low-density nickel-based high-temperature alloy is a directional columnar crystal high-temperature alloy or a single crystal high-temperature alloy, then: in the low-density nickel-based high-temperature alloy, the size of the carbides is 1-600 μm, and the size of the micropores is 10-100 μm.
11. The low-density nickel-based high-temperature alloy according to any one of claims 1 to 4, characterized in that: The low-density nickel-based high-temperature alloy has a durability life of more than 80 hours at 1020°C / 137MPa; The low-density nickel-based high-temperature alloy has a durability life of greater than or equal to 45 hours at 760°C / 500MPa; The low-density nickel-based high-temperature alloy has a durability life of greater than or equal to 25 hours at 980°C / 216MPa; The low-density nickel-based high-temperature alloy has a durability life of greater than or equal to 60 hours under the conditions of 1000° C. / 135 MPa.
12. The method for preparing the low-density nickel-based high-temperature alloy according to claim 1, characterized in that: The low-density nickel-based high-temperature alloy is a directional columnar crystal high-temperature alloy or a single crystal high-temperature alloy, and the preparation method comprises the following steps: Melting step: After vacuum induction melting of the alloy raw materials, casting into a master alloy ingot, and then grinding the master alloy ingot to remove the oxide scale; Directional solidification step: using a directional solidification process to prepare the polished master alloy ingot into a directional columnar crystal high-temperature alloy part or a single crystal high-temperature alloy part; Heat treatment step: heat treating the oriented columnar crystal high temperature alloy part or the single crystal high temperature alloy part to obtain a low-density nickel-based high temperature alloy.
13. The method for preparing a low-density nickel-based high-temperature alloy according to claim 12, characterized in that: In the directional solidification step, the pouring temperature is 320-360° C. higher than the initial melting temperature of the low-density nickel-based high-temperature alloy.
14. The method for preparing a low-density nickel-based high-temperature alloy according to claim 13, characterized in that: The mold shell temperature is consistent with the pouring temperature; or the mold shell temperature is 20-30°C higher than the pouring temperature.
15. The method for preparing a low-density nickel-based high-temperature alloy according to claim 12, characterized in that: In the smelting step, high-temperature refining is performed first and then low-temperature refining is performed; wherein, the Ca element is added to the melt in the low-temperature refining stage; after the low-temperature refining, the melt is naturally cooled, and when a film appears on the surface of the alloy melt, high-purity argon gas is filled in the vacuum furnace, and when the amount of the filled argon gas reaches 3-5Pa, the Mg element is added, and then the melt is heated to 1550±20°C for casting to obtain a mother alloy ingot.
16. The method for preparing a low-density nickel-based high-temperature alloy according to claim 15, characterized in that: The temperature of the high temperature refining is 1550±20°C; the temperature of the low temperature refining is 100±30°C above the alloy liquidus.
17. The method for preparing a low-density nickel-based high-temperature alloy according to claim 1, characterized in that: The low-density nickel-based high-temperature alloy is an equiaxed high-temperature alloy, and the preparation method comprises the following steps: Melting step: After vacuum induction melting of the alloy raw materials, casting into a master alloy ingot, and then grinding the master alloy ingot to remove the oxide scale; Equiaxed directional solidification step: performing equiaxed crystal solidification treatment on the polished master alloy ingot to obtain an equiaxed crystal high-temperature alloy part; Heat treatment step: heat treating the equiaxed high-temperature alloy part to obtain a low-density nickel-based high-temperature alloy.
18. The method for preparing a low-density nickel-based high-temperature alloy according to claim 17, characterized in that: The refining temperature in the smelting step is 1550-1600° C. to volatilize the Mg element.
19. The method for preparing a low-density nickel-based high-temperature alloy according to claim 17, characterized in that: In the step of equiaxed solidification treatment: the pouring temperature is 150-200°C higher than the initial melting temperature of the low-density nickel-based high-temperature alloy, and the mold shell temperature is 350-480°C lower than the pouring temperature.
20. The method for preparing a low-density nickel-based high-temperature alloy according to claim 17, characterized in that: In the smelting step, high-temperature refining is performed first and then low-temperature refining is performed; wherein, the Ca element is added to the melt in the low-temperature refining stage; after the low-temperature refining, the melt is naturally cooled, and when a film appears on the surface of the alloy melt, high-purity argon gas is filled in the vacuum furnace, and when the amount of the filled argon gas reaches 3-5Pa, the Mg element is added, and then the melt is heated to 1550±20°C for casting to obtain a mother alloy ingot.
21. The method for preparing a low-density nickel-based high-temperature alloy according to claim 20, characterized in that: The temperature of the high temperature refining is 1550±20°C; the temperature of the low temperature refining is 100±30°C above the alloy liquidus.
22. The method for preparing a low-density nickel-based high-temperature alloy according to claim 12 or 17, characterized in that: The heat treatment step comprises: Solid solution homogenization treatment: the high temperature alloy part is kept at a temperature of 1200-1220°C for 3.8-4.2 hours, and then cooled in air or inert gas to obtain a high temperature alloy after solid solution homogenization treatment; wherein the high temperature alloy part is any one of a directional columnar crystal high temperature alloy part, a single crystal high temperature alloy part, and an equiaxed crystal high temperature alloy part; Primary aging treatment: keeping the high-temperature alloy after the solid solution homogenization treatment at a temperature of 1090-1110° C. for 3.8-4.2 hours, cooling in air or inert gas to obtain a high-temperature alloy after the primary aging treatment; Secondary aging treatment: The high-temperature alloy after the primary aging treatment is kept at a temperature of 860-880° C. for 23.8-24.2 hours, and then cooled in air or inert gas to obtain a low-density nickel-based high-temperature alloy.
23. The method for preparing a low-density nickel-based high-temperature alloy according to claim 22, characterized in that: In the step of solid solution homogenization treatment: the high temperature alloy part is placed in a heat treatment furnace and heated to 1200-1220°C at a heating rate of 8±2°C / min to prevent deformation or cracking of the alloy part due to excessive heating.
24. The method for preparing a low-density nickel-based high-temperature alloy according to claim 22, characterized in that: In the step of the primary aging treatment: the high-temperature alloy after the solid solution homogenization treatment is heated to 1090-1110° C. at a heating rate of 15±2° C. / min.
25. The method for preparing a low-density nickel-based high-temperature alloy according to claim 22, characterized in that: The high-temperature alloy after the primary aging treatment is heated to 860-880° C. at a heating rate of 20±2° C. / min.
Citation Information
Patent Citations
Nickel-based equiaxed crystal alloy containing yttrium and hafnium, heat treatment process and applications thereof
CN107630152A